Vascular and Microvascular Dysfunction Induced by Microgravity and Its Analogs in Humans: Mechanisms and Countermeasures - Navasiolava, Nastassia; Yuan, Ming; Murphy, Ronan; Robin, Adrien; Coupé, Mickael; Wang, Linjie; Alameddine, Asmaa; Gauquelin-Koch, Guillemette; Gharib, Claude; Li, Yinghui; Custaud, Marc-Antoine (Frontiers in Physiology, 2020)
Weightlessness and physical inactivity have deleterious cardiovascular effects. The space environment and its ground-based models offer conditions to study the cardiovascular effects of physical inactivity in the absence of other vascular risk factors, particularly at the macro- and microcirculatory levels. However, the mechanisms involved in vascular dysfunction and remodeling are not sufficiently studied in the context of weightlessness and its analogs including models of physical inactivity. Here, we summarize vascular and microvascular changes induced by space flight and observed in models of microgravity and physical inactivity and review the effects of prophylactic strategies (i.e., countermeasures) on vascular and microvascular function. We discuss physical (e.g., exercise, vibration, lower body negative pressure, artificial gravity) and nutritional/pharmacological (e.g., caloric restriction, resveratrol and other vegetal extracts) countermeasures. Currently, exercise countermeasure appears to be the most effective to protect vascular function. Although pharmacological countermeasures are not currently considered to fight vascular changes due to microgravity, nutritional countermeasures are very promising. Dietary supplements/natural health products, especially plant extracts, should be extensively studied. The best prophylactic strategy is likely a combination of countermeasures that are effective not only at the cardiovascular level but also for the organism as a whole, but this strategy remains to be determined.